(untitled) (Journal of Pathology of Nepal, 2015)
The histopathological diagnosis plays a major role in the treatment of diseases. Errors in these reports affect patient care. Hence, it is of utmost importance for all practitioners of this specialty to be aware of possible errors in histopathology laboratories and the means to minimize them. As with other disciplines of laboratory medicine, errors can occur in the pre-analytical, analytical and post analytical phase. The concept of quality and its control should be applied to all phases to curb errors. Audit can be used as a tool to generate information about the background level of errors in pathology which in turn can be used to reduce and avoid errors in histopathology laboratory. Furthermore, accreditation is a means to ensure patient safety and best quality assurance.